Evaluation of biodeterioration and the dynamic modulus of elasticity of wood in ten fast-growing tropical species in costa rica exposed to field testing - Moya-Roque, Róger (Statny Drevarsky Vyskumny Ustav, 2015)
In tropical regions, it is possible to produce a large variety of timber species in plantation conditions. However, wood from these trees has low natural durability. Biodeterioration and the dynamic modulus of elasticity of wood (dMOE) were evaluated in 10 fast-growing tree species in Costa Rica during a 36-month exposure field test. Results showed a reduction in wood density of up to 50-80% of the dMOE in non-treated wood. Treatment with preservatives (Wolmanit CX-10) increased the wood's durability. In all species studied, loss in wood density decreased with absorption of the preservative. In the remaining species, we did not find that absorption of the preservative affected the loss of density or dMOE. Loss of wood density and dMOE were greatest in the first months of exposure, and loss of dMOE was greater than loss of wood density. Lastly, species were grouped by durability: Alnus acuminata was the species with the lowest endurance, while species Terminalia oblonga, Gmelina arborea, and Vochysia guatemalensis with low durability were grouped. The species Bombapcis quinata, Terminalia amazonia, and Cupressus lusitanica composed the intermediate durability group. A.mangium was the species with the highest wood durability. Swietenia macrophylla and Tectona grandis also had high wood durability, but lower than Acacia mangium. © 2015, Statny Drevarsky Vyskumny Ustav. All rights reserved.
https://www.scopus.com/inward/record.url?eid=2-s2.0-84937937341&partnerID=40&md5=55bdcc62b1281045bd8251d3d6e19eab
Keywords: Biodegadación; Bosques; Elasticidad; Durabilidad; Plantanciones; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Product science::Wood fibre and forest products